Petrocapitalism, displacement, and (im)mobilities in Imbolo Mbue’s How Beautiful We Were - Katarzyna Więckowska (Tydskrif vir Letterkunde)
In this article, I analyse the movement of human and nonhuman bodies in Imbolo Mbue’s How Beautiful We Were (2021). I argue that the depiction of the environmental and social damage caused by oil extraction in the novel resists the dominant discourse of the Anthropocene by refusing to universalise the threats produced by ecological crisis, embedding environmental vulnerability within histories of colonial violence and forced displacement and particularising the bodies that bear the cost of disasters. My reading of toxicity, the flow of capital, and networks of power demonstrates how agency is shaped by mobility, immobility, and attachment to place and points to the possibilities of resistance and change outlined in the book. How Beautiful We Were deploys multiple narrators and adopts an innovative way of telling the community’s story to convey the multigenerational and ongoing nature of postcolonial trauma. I argue that the use of petro-magic-realism and we-narrative makes the novel an example of collective climate witnessing and provides a means to combat environmental forgetting. Although the shift from forced immobility to forced mobility depicted in Mbue’s book may point to dark times ahead, I propose to interpret the focus on children as allowing for imagining the future as a time of positive transformation.